Pengaruh Model Blended Learning terhadap Kemandirian Belajar Siswa Kelas VIII SMP Karya Utama Dolok Masihul - Rizky Fadillah; Risna Mira Bella Saragih; Yumira Simamora (Departement of Mathematics Education, 2023)
The purpose of this research is to determine whether or not blended learning models increase students' capacity to learn independently. For this study, we used a convenience sample of eighth graders from SMP Karya Utama Dolok Masihul for the 2022-2023 school year as both the population and the sample. Questions and questionnaires were used to collect information for this study. The average score on the pretest was 38.4, the average score on the posttest was 61.1, and the average score on the questionnaire was 70.4. Based on the study's findings, it is known that students at SMP Karya Utama Dolok Masihul using a blended learning model on student learning independence obtained a mean score of 61.11. This means that students' learning outcomes are still classified as relatively low. Reasons for this include students' own lack of motivation to learn and the inability to participate in hands-on learning activities due to a lack of access to mobile devices. The study's author concluded that schools could do better to incorporate technological advances into their teaching and learning of mathematics. As a means of ensuring that both educators and students remain abreast of evolving technological capabilities, and to pique students' curiosity and motivate them to learn more on their own accord.